Pengaruh Promosi Kesehatan terhadap Pemahaman Remaja Putri mengenai Pencegahan Stunting di Madrasah Aliyah Persiapan Negeri 4 Medan - Sari, Eni Puspita; Dameria; Simanjuntak, Mafe Robbi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Nutritional problems affecting adolescent girls include short stature (stunting), anemia, Chronic Energy Deficiency (CED), obesity, and fetal growth restriction during adolescent pregnancies. These nutritional issues arise from improper dietary behaviors. Adolescent girls generally exhibit unhealthy eating habits, which, if continued, can negatively impact their reproductive health and nutritional status. This study employs a quantitative research approach with a quasi-experimental design and utilizes t-tests. The population and sample for this study consisted of 30 adolescent girls from class XI at the Medan 4 State Preparatory Madrasah Aliyah School. The results indicated significant differences in the knowledge, attitudes, and behaviors of the adolescent girls between the pre-test and post-test conducted by health workers.